European Union Non-Discrimination Law and Intersectionality : Investigating the Triangle of Racial, Gender and Disability Discrimination. - Schiek, Dagmar (Ashgate Pub., 2011)
The book contributes to a critical reflection of current legislative and jurisprudential developments in Non-Discrimination Law, focusing on the European Union. The work provides coherent coverage of the legal dimension of intersectionality in the EU's non-discrimination regime. It will be a valuable resource for researchers, academics and those working in the area of EU non-discrimination law and policy.